Hobbes as Political Theologian. Issue 1 (1st February 2013) - Rose, Matthew
Abstract: Although an orphaned subject among scholars of religion, the theology of Thomas Hobbes is now among the most contested issues in Hobbes studies and the study of early liberal political theory. This essay maps the state of the question and offers a theological appraisal of it. In so doing it attempts to critique a leading reading of Hobbes's Leviathan by highlighting its attack on civil religion and endorsement of a biblical political theology. The relationship between Hobbes's political and theological views in Leviathan also receives sustained attention.